The evaluation of functional heart condition with machine learning algorithms - Overchuk K. V.; Lezhnina I. A. Inna Alekseevna; Uvarov A. A. Aleksandr Andreevich; Perchatkin V. A.; Lvova A. B. (2017, 2017)
Title screen